Combined 18F-NaF and 18F-FDG PET/CT in the Evaluation of Sarcoma Patients. (September 2015) - Jackson, Tatianie; Mosci, Camila; von Eyben, Rie; Mittra, Erik; Ganjoo, Kristen; Biswal, Sandip; Gambhir, Sanjiv Sam; Iagaru, Andrei
Abstract : Purpose: The combined administration of 18 F-NaF and 18 F-FDG in a single PET/CT scan has the potential to improve patient convenience and cancer detection. Here we report the use of this approach for patients with sarcomas. Patients and Methods: This is a retrospective review of 21 patients (12 men, 9 women; age, 19–66 years) with biopsy-proven sarcomas who had separate 18 F-NaF PET/CT, 18 F-FDG PET/CT, and combined 18 F-NaF/ 18 F-FDG PET/CT scans for evaluation of malignancy. Two board-certified nuclear medicine physicians and 1 board-certified musculoskeletal radiologist were randomly assigned to review the scans. Results were analyzed for sensitivity and specificity, using linear regression and receiver operating characteristics. Results: A total of 13 patients had metastatic disease on 18 F-NaF PET/CT, 18 F-FDG PET/CT, and combined 18 F-NaF/ 18 F-FDG PET/CT. Skeletal disease was more extensive on the 18 F-NaF PET/CT scan than on the 18 F-FDG PET/CT in 3 patients, whereas in 1 patient, 18 F-FDG PET/CT showed skeletal disease and the 18 F-NaF PET/CT was negative. Extraskeletal lesions were detected on both 18 F-FDG and combined 18 F-NaF/ 18 F-FDG PET/CT in 20 patients, with 1 discordant finding in the lung. Conclusions: The combined 18 F-NaF/ 18 F-FDG PET/CT scan allows for accurate evaluation of sarcoma patients. Further evaluation of this proposed imaging modality is warranted to identify the most suitable clinical scenarios, including initial treatment strategy and evaluation of response to therapy.